Latvia Tax Review - World Bank (World Bank, Washington, DC, 2020)
Latvia’s Ministry of Finance requested the World Bank to collaborate on a review of the country’s tax system as input for the design a medium-term tax strategy. The motivation behind the tax review is to find options to increase tax revenues by three percentage points of GDP to reach a target tax-to-GDP ratio of 33 percent in the medium term.1 In Latvia, tax revenues are lower than predicted for its income level and institutional development. Latvia’s tax policy needs to be restructured to support economic development and raise living standards. The speed of convergence in Latvia to average income levels in the European Union (EU) was impressive until the 2008-2009 crisis, but since then output recovery has been fast but not rapid enough for real GDP to return to pre-crisis level. A critical challenge then is to boost productivity growth in the economy: the level of productivity is low relative to OECD economies and its growth has slowed notably since the crisis. Increasing labor productivity is particularly important if overall productivity is to rise: informality and inactivity reduce both labor activity and productivity. Increased investment in skills and good health are an important part of the labor productivity and participation story—particularly as Latvia rapidly ages. But reducing the reliance of the tax system on low-skilled labor is also a key policy challenge. Latvia’s tax system puts substantially more of a burden on labor compared to capital or consumption. This is all the more concerning given that wages for much of the population are low and so the current flat income tax structure has implications for social inclusion and poverty. Inequality of (after-tax) disposable income in Latvia is one of the highest in the EU, with only Bulgaria, Romania and Lithuania having higher inequality. The tax system entails distributional choices and one of the objectives of the review is to look at options to improve the equity of the system. Here both vertical equity, i.e. taxing less those of lower income, and horizontal equity, i.e. taxing the same those in economically similar situations, are of importance. Governments are inevitably confronted with an equity-efficiency trade-off: higher taxes on the richer parts of the population, to raise revenue and to finance benefits for poorer groups, can distort the economic incentives for work, entrepreneurship, saving and risk-taking of middle- and higher-income individuals. At the same time, redistribution to low-income individuals, through tax credits or benefits, could weaken labor supply incentives. On the other hand, fairness, or equity is an important consideration for widespread acceptance and sustainability of the tax system.